SOLVING GRAND CHALLENGES TOGETHER: A BRAZIL-NORWAY APPROACH TO TEACHING COLLABORATIVE DESIGN AND PROTOTYPING OF ASSISTIVE TECHNOLOGIES AND PRODUCTS FOR INDEPENDENT LIVING - Sandnes, Frode Eika; Medola, Fausto Orsi [UNESP]; Berg, Arild; Rodrigues, Osmar Vicente [UNESP]; Mirtaheri, Peyman; Gjovaag, Terje; Berg, A.; Bohemia, E.; Buck, L.; Gulden, T.; Kovacevic, A.; Pavel, N. (Design Soc, 2017)
This paper describes the roadmap for a long term strategic internationalization project involving two key higher education institutions in Norway and Brazil. The project involves six different yet related areas of knowledge, namely collaborative design, ergonomics, rehabilitation, human computer interaction and rapid prototyping. One of the global grand challenges includes how to ensure dignified and independent living for the increasingly aging population as the body functions decay naturally with age. The aims are to generate new knowledge and produce highly skilled graduates that are able to work efficiently in multidisciplinary teams to support and orient solutions to real problems related to independent living for the population in general and assistive devices for people with disabilities in particular. The theoretical framework is based on pedagogical ideas on social learning and Hofstede's cultural analysis. The research design of the project involves case studies of real-world problems and practices where students are linked with a rehabilitation centre. To reach the goals new courses at both bachelor and master levels are developed, joint workshops are held, high volume student and teacher exchanges are conducted as well as student and teacher internships. This paper describes the project and discusses how cultural differences are likely to affect the collaboration.
Keywords: Internationalization; cultural differences; assistive technologies; universal design; 3D-printing; biomedical engineering; independent living